Sex‐specific responses to territorial intrusions in a communication network: Evidence from radio‐tagged great tits - Snijders, Lysanne (Ecol Evol, 2017)
Signals play a key role in the ecology and evolution of animal populations, influencing processes such as sexual selection and conflict resolution. In many species, sexually selected signals have a dual function: attracting mates and repelling rivals. Yet, to what extent males and females under natural conditions differentially respond to such signals remains poorly understood, due to a lack of field studies that simultaneously track both sexes. Using a novel spatial tracking system, we tested whether or not the spatial behavior of male and female great tits (Parus major) changes in relation to the vocal response of a territorial male neighbor to an intruder. We tracked the spatial behavior of male and female great tits (N = 44), 1 hr before and 1 hr after simulating territory intrusions, employing automatized Encounternet radio‐tracking technology. We recorded the spatial and vocal response of the challenged males and quantified attraction and repulsion of neighboring males and females to the intrusion site. We additionally quantified the direct proximity network of the challenged male. The strength of a male's vocal response to an intruder induced sex‐dependent movements in the neighborhood, via female attraction and male repulsion. Stronger vocal responders were older and in better body condition. The proximity networks of the male vocal responders, including the number of sex‐dependent connections and average time spent with connections, however, did not change directly following the intrusion. The effects on neighbor movements suggest that the strength of a male's vocal response can provide relevant social information to both the males and the females in the neighborhood, resulting in both sexes adjusting their spatial behavior in contrasting ways, while the social proximity network remained stable. This study underlines the importance of “silent” eavesdroppers within communication networks for studying the dual functioning and evolution of sexually selected signals.